(3GdJPcQI aj GdbQGAGJs - (3YHO GdefYe Hf YHjO Gddg Hf ZdHhf Hf GdeHGQc, CHh GdWqjH, J (B389 (3g` s
(3ChdgG (B:s
(3ShQI GdCfYGe bQC CHh HcQ hMeRI hGdcSGFi hjYbhH ef jUQa Yfg HaJM GdjGA hcSQ GdQGA , hbQC GdHGbhf HVe GdjGA haJM GdQGA s
(3BNQgG (B:s
(3BNQ GdehLhO efg ef HGH PcQ JcHjQ GdHRi ef (B" (3hGdVMi (B" (3bhdg (B: (3hCeG MLI GdJcHjQ abQCJ Ydi CHj GdMSf GddZhi , hELGRI di bGd (B: (3MOKfG GHf eLGgO bGd (B: (3MOKfG YcQeI Hf SdejGf s
(3HGdfSNI JeRjb ai CYdi HYV GdUaMGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs